2015
DOI: 10.1007/s11192-015-1547-0
|View full text |Cite|
|
Sign up to set email alerts
|

The open access advantage considering citation, article usage and social media attention

Abstract: Abstract:In this study, we compare the difference in the impact between open access (OA) and non-open access (non-OA) articles. 1761 Nature Communications articles published from 1 Jan. 2012 to 31 Aug. 2013 are selected as our research objects, including 587 OA articles and 1174 non-OA articles. Citation data and daily updated article-level metrics data are harvested directly from the platform of nature.com. Data is analyzed from the static versus temporal-dynamic perspectives. The OA citation advantage is con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(162 citation statements)
references
References 22 publications
6
143
0
8
Order By: Relevance
“…The case for open access has been extensively reported in the literature [14,16,[31][32][33] 10 . Essentially, advocates of open access want full access to, and use of, published scientific articles, moved by the core argument that publicly funded universities and granting bodies have a moral duty to make academic research output available on the web at no charge.…”
Section: Open Access: the Right To Knowledgementioning
confidence: 99%
“…The case for open access has been extensively reported in the literature [14,16,[31][32][33] 10 . Essentially, advocates of open access want full access to, and use of, published scientific articles, moved by the core argument that publicly funded universities and granting bodies have a moral duty to make academic research output available on the web at no charge.…”
Section: Open Access: the Right To Knowledgementioning
confidence: 99%
“…They confirmed Open Access Altmetric Advantage which means that OA articles received more altmetrics than non-OA articles. Wang (107) confirmed the OACA and download advantages. Alhoori's (110) study reported a significant correlation between citations and altmetrics for NOA and OA articles.…”
Section: Resultsmentioning
confidence: 76%
“…Four studies (105)(106)(107)110) pointed the correlations of citations, downloads and altmetrics between OA and non-OA articles. They confirmed Open Access Altmetric Advantage which means that OA articles received more altmetrics than non-OA articles.…”
Section: Resultsmentioning
confidence: 99%
“…The known effect of increased downloads for OA articles (Davis, 2011;Wang et al, 2015) means article level use counts will be higher than non-OA articles when calculating cost per use. Unlike the traditional publishing model where many institutions pay each for their own institution's use, for OA fund payments one institution pays for all use, including their own and that of other institutions and individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Two different randomized controlled trials found OA articles had higher levels of downloads, and a greater number of addresses downloading them, than non-OA articles (Davis, 2011;Davis, Lewenstein, Simon, Booth, & Connolly, 2008). Two other studies found that usage of OA articles is higher not only initially after publication but continuing over time (Wang, Liu, Mao, & Fang, 2015;Wang, Mao, Xu, & Zhang, 2014). From these studies, it can be anticipated that usage counts for APC funded articles will be relatively high compared to traditional-model publishing, particularly when considered cumulatively.…”
Section: Literature Reviewmentioning
confidence: 98%